YOUTH AND YOUTH POLICY IN THE POST-SOVIET STATES - D. A. Tsyunik (Проблемы постсоветского пространства, 2017)
Young people as a special age category and social group are the object of studying the complex of humanities — political science, sociology, political philosophy, political psychology, cultural studies, conflict studies, etc. The need for youth research is conditioned by the formation of an actual strategy and tactics of the state youth policy, which can contribute to the increase Effectiveness of the activities of political institutions, authorities and government, to promote the dynamic development of the state Society and society. Youth policy is one of the most important factors in the modernization of the state, therefore it is important to develop tools for measuring the parameters of the systemic change of society under the influence, with the participation of emerging, developing youth organizations.The theme of the study of the problems of youth is important in connection with the activation of the use of technologies for the recruitment of youth into political organizations (party organizations), which strengthens the competitive struggle of various political forces for influencing the younger generation of citizens as potentially active citizens who are supporters or opponents of certain parties.The urgency of the study is also conditioned by the processes of building the rule of law and the development of civil society institutions. This process is impossible without overcoming the political passivity, the apolitical nature of the younger generation. Youth organizations can become an important element. The political participation of the youth of Russian society is non-systemic, moreover, a significant part of the youth is politically inactive, indifferent to political changes. Studying the mechanisms for overcoming this state, increasing the involvement of young people in the political life of society is an important not only research, but also a practical task.At the present stage of development, youth movements and organizations occupy a rather significant place in the political process. Every year the number of new organizations is growing. Young people, this is quite an impulsive mass, which is easily influenced by the authority of the leader, which impresses them. Young people, through accession to a youth organization, have the right and the opportunity to influence the political process. Youth movements and organizations are in direct relationship with the political system. Politics is not possible without properly motivated youth, youth movements and organizations, as well as the youth movement is not possible without politics, there is an important role of political organizations in the political arena.This paper examines the problems of transformation of the youth policy of the ex-USSR countries in view of political developments in the post-Soviet region and in the world. It carried out a review of mechanisms of the implementation of the youth policy amid renewed values orientation structure of the younger generation of the post-Soviet countries. Historical account of formation of youth policy in certain select countries reviewed in this article.